STUDI TINGKAT KESESUIAN LAHAN UNTUK TANAMAN GAMBIR DI KECAMATAN KAPUR IX KABUPATEN LIMA PULUH KOTA - Hafsah, Ainul; Hermon, Dedi; Yuherman, Yuherman (Pendidikan Geografi, 2013)
This research was conducted with the purpose of 1) investigate the characteristics of suitable land to plant gambier 2) to land units which are suitable to plant gambier 3) determine the spatial distribution of land suitability for crops gambier in District IX Limestone District Fifty Cities. Land units that exist in the study area consists of 27 land units and samples taken only 18 land units. The sampling technique is to use the technique of sampling area (area sampling) based with a variety of land units, sampling with stratified random sampling method is a technique taken sampling strata (level) land units. Analysis of the data used is descriptive analysis in the form of tables of comparison between the characteristics of the soil (soil texture, slope, solum depth, drainage, elevation, pH, and surface rock outcrop) compared with the suitability of land for crop gambier. The results showed that: 1) there are differences in the characteristics of the land that is land drainage, soil texture, slope, solum depth, height (elevation), the stone surface, rock outcrops and soil pH on each unit of land in Limestone District IX District Fifty Cities , 2) the presence of the suitability of land for crop diversity gambier in District IX Limestone District Fifty Cities. Satuanlahan accordance with the conditions contained in the research area on land units V3.Tmgr.III.Ht.Pod, V4.Tmgr.IV.Ht.Lat,V4.Tmgr.IV.Ht.And,V3.Tmgr.III.Sm.Pod,V3.Tmgr.III.Kc.Pod,V1.Qtp.I.Ut.Pod and V4.Tmgr.IV.Ut.Lat somewhat appropriate category located on landunits V3.Qpt.III.Ht.Pod,V4.Tmgr.IV.Sm.Pod,V3.Tmgr.III.Ut.Pod,V4.Tmgr.IV.Kc.Pod,V1.Qtp.I.Ht.Pod,V3.Tmgr.III.Ut.Lat,V1.Qtp.I.Kb.Pod,V4.Tmgr.IV.Kc.Lat,V3.Tmgr.III.Kc.Lat,V3.Tmgr.III.Sm.Lat and V4.Tmgr.IV.Ut.Lat. 3) there is a spatial distribution of land to plant gambier kesesesuaian in District IX Limestone District Fifty-Cities on location in Nagari Nagari Koto Sialang and Lamo included in the first category is land suitable for crop gambier, in Muara Paiti Nagari, Nagari Nagari gelugur and Lubuk Alai including category II is a little land suitable for crops and gambier in Nagari Nagari Koto Rise and High Durian included in category I and II is suitable land and land suitable for crops rather gambier.